ROLLING FRICTION POWER LOSSES TEST IN HIGHLY LOADED SUPPORTS UNITS OF CONTINUOUS ACTION ASSEMBLIES - Кузьо, Ігор Володимирович; Гурський, Володимир Миколайович; Сорокіна, Тетяна Миколаївна; Носко, Павло Леонідович; Башта, Олександр Васильович (Problems of Friction and Wear, 2021)
In the General case, the losses due to rolling and sliding friction in the support units can reach up to 30% of the total drive power, which can be P = 1000-2000 kW and more. There are also other mechanical losses due to rolling and sliding friction, in particular in the gearing of the unit rotation. The article presents the results of experimental studies of the rolling friction process of two cylindrical rollers on the experimental stand, which simulates the rotate assembly support unit operation. The development of the experimental stand is based on three criteria of similarity (geometric, kinematic and dynamic) to the existing equipment. The stand is made with a geometric scale of rolling pair M 1:10. The load in the contact was determined under the condition of equality of contact pressures arising between the bandage and the roller on the full-scale equipment and the investigated rollers on the experimental stand. The defining force and kinematic characteristics of the experimental model are obtained. The moment of rolling friction is determined depending on the circular rolling speed and radial load on the rolling pair. The value of the steel rollers rolling friction coefficient limits is recommended based on they experimentally obtained results. It is determined that the value of the rolling friction coefficient can fluctuate due to changes in rolling speed within certain limits, and then increase with further increase in speed. The rolling frictional coefficients regularities of changes from the rolling speed and the contact pressures radial load, which are corresponding with the real values in basic support units of industrial rotate kilns, are established. Based on this, the loss of power due to rolling friction in the support units of large rotating units, continuous operation, in particular drum dryers, screens, etc. is determined based on the recommended values of the rolling friction coefficient.